1994
DOI: 10.1111/j.1365-2494.1994.tb01978.x
|View full text |Cite
|
Sign up to set email alerts
|

The implications of controlling grazed sward height for the operation and productivity of upland sheep systems in the UK. 1. Effects of two annual stocking rates in combination with two sward height profiles

Abstract: The consequences of controlling sward height at two levels, around 5 cm (HS) and around 3·5 cm (LS), during spring and summer by adjusting weekly the proportion of the areas grazed in response to changes in rate of herbage production and utilizing the surplus pasture areas to conserve winter fodder were studied over three complete years for Greyface ewes with their lambs at 15ha−1 (SR15) and 10ha−1 (SR10). The rules used to control grazed sward height resulted in acceptable sward height control in three of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…For perennial ryegrass swards, with high nitrogen supply, the sward height recommendations are accurate (Hodgson 1985, Parsons 1988. They vary according to the field and the animal type (Le Du et al 1981, Maxwell et al 1994. For other forms of grazing management than continuous grazing, there is not such a global indicator which allows one to decide how much grazing area to add or to remove to maintain a high grazing intensity on a set of grazed fields throughout a growing season.…”
mentioning
confidence: 99%
“…For perennial ryegrass swards, with high nitrogen supply, the sward height recommendations are accurate (Hodgson 1985, Parsons 1988. They vary according to the field and the animal type (Le Du et al 1981, Maxwell et al 1994. For other forms of grazing management than continuous grazing, there is not such a global indicator which allows one to decide how much grazing area to add or to remove to maintain a high grazing intensity on a set of grazed fields throughout a growing season.…”
mentioning
confidence: 99%
“…Sward height was controlled by the closing of areas of pasture surplus to grazing requirements; the pasture accumulated on the ungrazed areas was conserved as silage for use in the winter and the yield obtained was measured (Maxwell et al ., 1994). The consistently grazed subplot areas were common to all 3 years.…”
Section: Sward Height Management Supplementary Feeding and Productiomentioning
confidence: 99%
“…In the first four experiments in this series, the aim was to test the validity and feasibility of controlling grazed sward height within specified limits in the operational management of sheep systems with respect to stocking rate (Maxwell et al ., 1994), level of nitrogen fertilizer application (Sibbald et al ., 1994), genotype of ewe (Maxwell et al ., 1997) and seasonal pattern of application of nitrogen fertilizer (Maxwell et al ., 1998). Provided that the grazed sward height can be controlled between 3·5 and 5·5 cm during the period of lactation and that supplementation is offered when sward height falls below 3·5 cm during the early lactation and mating periods, it was found that flock performance, indicated by lamb liveweight gain and ewe reproduction rate, was within acceptable limits irrespective of annual stocking rate, level and pattern of nitrogen fertilizer application or genotype of ewe.…”
Section: Introductionmentioning
confidence: 99%
“…Swards were managed in relation to grazing and conservation as described in Sibbald et al (1994). Sward and animal measurements were undertaken as described in Maxwell et al (1994) and conservation measurements as described in Sibbald et al (1994).…”
Section: Experiments 1 Andmentioning
confidence: 99%